Sarcodia suieae Acetyl-Xylogalactan Regulates Nile Tilapia (Oreochromis niloticus) Tissue Phagocytotic Activity and Serum Indices - Po-Kai Pan; Tsung-Meng Wu; Chiu-Ming Wen; Yin-Yu Chen; Yu-Sheng Wu (Journal of Marine Science and Engineering, 2021)
Sarcodia suieae acetyl-xylogalactan was reported to induce macrophage polarisation, and could positively regulate macrophage activation. In this study, we evaluated the effect of Sarcodia suieae acetyl-xylogalactan on the Nile tilapia. First, we assessed the influence of acetyl-xylogalactan on the survival, glucose uptake, and phagocytic activity of tilapia head kidney (THK) melanomacrophage, and observed increased proliferation of these cells in the MTT assay after 12 and 24 h of treatment. Glucose uptake increased in THK melanomacrophage treated with 20 and 30 μg acetyl-xylogalactan for 24 h. Their phagocytic activity was positively enhanced following exposure to acetyl-xylogalactan. Nile tilapia were fed with acetyl-xylogalactan for 4 weeks. At the end of the experiment, Nile tilapia were sacrificed, and the lipopolysaccharide-induced liver and head-kidney apoptosis was examined under reducing conditions in comparison with controls. The phagocytic activities of liver and head-kidney cells were enhanced after 4 weeks of feeding. Blood biochemical analysis revealed a reduction in glutamic oxaloacetic transaminase (GOT) and glutamic pyruvic transaminase (GPT) levels after 4 weeks of feeding. Combined with in vitro and in vivo experiments results, the extracted S. suieae acetyl-xylogalactan could directly induce THK melanomacrophage proliferation, glucose uptake, and phagocytic activity. Acetyl-xylogalactan was able to induce Nile tilapia liver and head-kidney resident macrophage activity, and reduced LPS-induced liver and head-kidney cell apoptosis. S. suieae acetyl-xylogalactan may modulate Nile tilapia macrophage activation by polarising them into M1 macrophages to improve the Nile tilapia nonspecific immune response.